Morphological characteristics of water mite larvae of the genus Arrenurus Duges, 1834, with notes on the phylogeny of the genus and an identification key - Zawal, Andrzej (Zootaxa, 2008)
The larval characteristics of 42 European Arrenurus species are provided, based on earlier descriptions. Diagnostic characters are elucidated. The division of the genus into the subgenera Arrenurus s. str., Micrarrenurus, Megaluracarus, Micruracarus, and Truncaturus has been retained. Principal Components Analysis (PCA) and phylogenetic analysis using the Maximum Parsimony (MP) method were used to construct a phylogenetic tree of the genus. Recommendations on changes to the traditional subgeneric systematics are given, concerning mainly the subgenera Micruracarus and Truncaturus as well as subgeneric allocation of Arrenurus nobilis Neuman which is transferred from Arrenurus s. str. to Micruracarus. An identification key, supplemented with diagnostic descriptions of individual species, is supplied.